Achieving the Paris Climate Agreement goals : global and regional 100% renewable energy scenarios with non-energy GHG pathways for +1.5°C and +2°C - Teske, Sven; Giurco, Damien; Morris, Tom; Nagrath, Kriti; Mey, Franziska (Cham, Switzerland : Springer Open, 2019)
This open access book presents detailed pathways to achieve 100% renewable energy by 2050, globally and across ten geographical regions. Based on state-of-the-art scenario modelling, it provides the vital missing link between renewable energy targets and the measures needed to achieve them. Bringing together the latest research in climate science, renewable energy technology, employment and resource impacts, the book breaks new ground by covering all the elements essential to achieving the ambitious climate mitigation targets set out in the Paris Climate Agreement. For example, sectoral implementation pathways, with special emphasis on differences between developed and developing countries and regional conditions, provide tools to implement the scenarios globally and domestically. Non-energy greenhouse gas mitigation scenarios define a sustainable pathway for land-use change and the agricultural sector. Furthermore, results of the impact of the scenarios on employment and mineral and resource requirements provide vital insight on economic and resource management implications. The book clearly demonstrates that the goals of the Paris Agreement are achievable and feasible with current technology and are beneficial in economic and employment terms. It is essential reading for anyone with responsibility for implementing renewable energy or climate targets internationally or domestically, including climate policy negotiators, policy-makers at all levels of government, businesses with renewable energy commitments, researchers and the renewable energy industry.
Keywords: RECURSOS ENERGETICOS RENOVABLES; CALENTAMIENTO GLOBAL -- PREVENCIÓN; CAMBIOS CLIMATICOS; DESARROLLO SOSTENIBLE